Estimation of SMPS’ Conducted Emission According to CISPR Standards - Robert Malczyk; Mateusz Bara; Haihui Lu (Applied Sciences, 2022)
Switched-mode power supplies are very efficient and commonly used components in products nowadays. However, due to currents switched at a high frequency, the conducted emission test is a high concern for designers. The market is increasingly demanding in terms of the size of the components and their efficiency. In order to meet market requirements and reduce the size of the power supply (both built into the product or standalone), the switching frequency of the SMPS is rising; hence the base frequency and its harmonics cover a frequency range of the conducted emission test. Due to this fact, the estimation of the test result becomes a great concern for the designer. This paper describes the approach that one can utilize to estimate the switched-mode power supply’s conducted emission as a standalone component with simulation tools using only the power supply being designed. The workflow, which is the result of this work, can be utilized in order to optimize the design of power suppliers from the conducted emission perspective.